Cash or Stock? The Impact of Payment Method on Acquirer Value Creation in Nordic M&A Transactions - Hiltunen, Roope (My University, 2026)
This thesis examines how the method of payment in Nordic mergers and acquisitions shapes both the stock market’s immediate reaction to acquisition announcements and the acquiring firm’s subsequent performance. While prior evidence, largely based on the U.S markets, often links stock-financed deals to adverse selection and weaker market responses, Nordic institutional features may alter how investors interpret payment choice. Using a Nordic M&A sample, this thesis conducts an announcement-period event study and complements it with multivariate event-window regressions. To assess long-run outcomes, panel regressions are estimated for operating performance and valuation measures over several post-deal horizons. The thesis also employs propensity score matching based on pre-deal covariates to improve comparability between cash- and stock-financed deals. Balance diagnostics indicate substantial improvement in covariate balance after matching. The findings are interpreted against the Nordic governance setting and ownership structure: concentrated ownership, high disclosure and listed acquirers’ financing choices can alter the information content of the payment method relative to U.S. -centric evidence. The analysis reports associations rather than strong causal claims, and the scope is limited to listed acquirers and the market conditions of the study period. In this way, the study complements the payment-method literature by highlighting a context where signals may reflect contracting and governance features rather than opportunistic timing. The results indicate that stock-financed acquisitions receive more favorable announcement-period abnormal returns than cash-financed acquisitions, reversing the canonical prediction. In the longer run, raw estimates suggest a cash advantage in operating performance when measured by ROA, but this difference attenuates markedly in the matched sample. Across ROIC and Tobin’s Q, long-run differences are weak and not robust. Overall, the findings highlight that payment method signals are context-dependent and that selection and deal comparability are central to interpreting cash-stock contrasts in Nordic M&A.

Tässä tutkielmassa tarkastellaan, miten yrityskaupan maksutapa vaikuttaa markkinoiden välittömään reaktioon yrityskauppauutisen julkistuksen yhteydessä sekä ostajayhtiön myöhempään suoriutumiseen Pohjoismaisessa markkinakontekstissa. Aiempi, pitkälti Yhdysvaltoihin painottuva kirjallisuus, liittää osakevastikkeen usein informaatioepäsymmetriaan ja heikompaan markkinareaktioon, mutta pohjoismainen instituutioympäristö voi muuttaa maksutavan tulkintaa. Aineistona käytetään pohjoismaista yrityskauppajoukkoa. Lyhyen aikavälin vaikutuksia analysoidaan tapahtumatutkimuksella ja monimuuttujaregressioilla eri tapahtumaikkunoissa. Pitkän aikavälin tarkastelussa estimoidaan paneeliregressioita sekä operatiivisille että arvostuspohjaisille mittareille käyttäen vertailuaseman parantamiseen propensity score matching -menetelmää. Tähän liitännäinen balanssidiagnostiikka osoittaa, että menetelmä parantaa kovariaattitasapainoa selvästi. Tuloksia tulkitaan pohjoismaisen hallintoympäristön ja omistusrakenteen valossa: keskittynyt omistus, korkea läpinäkyvyys ja listattujen yhtiöiden rahoitusvaihtoehdot voivat muuttaa maksutavan informaatiosisältöä verrattuna aiempaan Yhdysvaltoihin painottuneeseen kirjallisuuteen. Analyysi keskittyy nimenomaan havaittuihin yhteyksiin ilman vahvoja kausaaliväitteitä, ja löydökset rajautuvat listattuihin ostajiin sekä tarkastelujakson markkinaolosuhteisiin. Näin ollen työ täydentää maksutapakirjallisuutta kontekstilla, jossa signaalit voivat heijastaa enemmän sopimus- ja hallintamekanismeja kuin opportunistista ajoitusta. Tulokset osoittavat, että osakevastikkeella rahoitetut yrityskaupat saavat Pohjoismaissa keskimäärin myönteisemmän julkistusreaktion kuin käteisvastikkeella rahoitetut kaupat. Pitkällä aikavälillä raaka-aineistolla estimoidut tulokset viittaavat käteiskauppojen parempaan operatiiviseen suoriutumiseen ROA:lla mitattuna, mutta ero pienenee selvästi matched-otoksessa. ROIC:n ja Tobinin Q:n osalta erot ovat heikkoja eikä niille löydy robustia tukea. Kokonaisuutena maksutavan informaatiosisältö vaikuttaa olevan kontekstisidonnainen, nostaen sekä valikoitumisen että vertailukelpoisuuden kriittisiksi tekijöiksi erojen tulkinnassa pohjoismaisissa yrityskaupoissa.
Keywords: Mergers and acquisitions; method of payment; event study; cumulative abnormal returns; propensity score matching; Nordic markets; selection; yrityskaupat; maksutapa; tapahtumatutkimus; epänormaalit tuotot; Pohjoismaat; valikoituminen